ANALISIS KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK PADA MATERI PERUBAHAN DAN PELESTARIAN LINGKUNGAN HIDUP FASE E SMA N 3 SOLOK - Ailsa Najma Rahmadani; Fitri Olvia Rahmi; Heffi Alberida; Muhyiatul Fadilah (Al-Alam: Islamic Science Education Journal, 2025)
Problem-solving ability is an essential competence that needs to be developed in students to face real-life problems, particularly those related to environmental issues. This study aimed to analyze students’ problem-solving abilities on the topic of environmental change and conservation for Phase E at SMA N 3 Solok. The research employed a descriptive quantitative approach. The research subjects were Phase E students of SMA N 3 Solok selected using a purposive sampling technique. The research instrument was a problem-solving ability test developed based on five indicators: defining the problem, examining the problem, planning solutions, implementing the plan, and evaluating the solution. The data were analyzed using percentage analysis techniques. The results showed that students’ problem-solving abilities were generally in the category of needing improvement. The indicator of defining the problem demonstrated better achievement compared to other indicators, while the indicators of examining the problem, planning solutions, implementing the plan, and evaluating the solution still require improvement. The findings of this study are expected to serve as a basis for developing learning strategies oriented toward improving students’ problem-solving abilities in the context of biology learning and sustainable environmental education. Keywords: problem-solving ability, environmental change, environmental conservation, Phase E, senior high school